IMROVING STUDENTS WRITING SKILL BY USING COMMUNICATIVE METHOD OF GRADE SEVEN AT DARMA SCHOOL IN MEDAN JOHOR - Kammer Tuahman Sipayung; Juliper Nainggolan; Sarah Evelyn Simanjuntak (Jurnal Scientia, 2023)
Writing is an activity to create a note or information on a media using script. The aim of this study to examine the improvement of students' writing skill at Darma Private Middle School in Medan Johor by implementing communicative method. To achieve the objectives of the research, the authors use classroom action reserach methods. This research involved seventh grade students at Darma Private Middle School Medan. The population of this research is fifty five students and the sample of this research is twenty five students. Data were analyzed qualitatively and quantitatively through writing tests. To improves students writing skills in English, proven to improve aspects of writing, vocabulary and grammar. This study figure out that students average on writing improve from the first cycle 61,2 to the second cycle 82,4. It can be as alternative way in teaching writing.